Enhancing Learning Interest in Mathematics Through Laboratory Methods in Education - Bille Geraldi (Institute of Computer Science (IOCS), 2024)
This research investigates the effectiveness of laboratory methods in increasing learning interest in mathematics. Through a comprehensive analysis of data collected from surveys, classroom observations, and interviews with educators and students, the study examines the impact of laboratory-based instruction on student engagement, conceptual understanding, and attitudes towards mathematics. The findings reveal a positive correlation between the implementation of laboratory methods and increased student enthusiasm for learning mathematical concepts. Students reported greater confidence in their mathematical abilities and a deeper appreciation for the relevance and applicability of mathematics in their daily lives. Moreover, the study highlights the importance of teacher practices, curriculum design, and professional development in maximizing the benefits of laboratory methods in mathematics instruction. The research contributes to our understanding of the transformative potential of laboratory-based instruction in mathematics education and provides valuable insights that can inform efforts to enhance mathematics education practice.